2018
DOI: 10.1373/jalm.2018.026393
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA for Early Cancer Detection

Abstract: Background Cancer cells release circulating tumor DNA (ctDNA) into the bloodstream, which can now be quantified and examined using novel high-throughput sequencing technologies. This has led to the emergence of the “liquid biopsy,” which proposes to analyze this genetic material and extract information on a patient's cancer using a simple blood draw. Content ctDNA has been detected in many advanced cancers. It has also been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…In cfDNA, for example, mutation allele frequency decreases with disease burden, leading to an increasing probability that there will not exist a single copy of a mutation in a 10 mL blood draw 36 . It is estimated 35,37 that tumors must reach volumes greater than 1,000 mm 3 (corresponding to allele frequencies of 0.01 %) for there to exist even one genome equivalent of tumor DNA in 4 mL of plasma. Our studies mirror these findings as the macrophage sensor could detect tumors up to 50-fold smaller in volume than possible with cfDNA mutation detection.…”
Section: Discussionmentioning
confidence: 99%
“…In cfDNA, for example, mutation allele frequency decreases with disease burden, leading to an increasing probability that there will not exist a single copy of a mutation in a 10 mL blood draw 36 . It is estimated 35,37 that tumors must reach volumes greater than 1,000 mm 3 (corresponding to allele frequencies of 0.01 %) for there to exist even one genome equivalent of tumor DNA in 4 mL of plasma. Our studies mirror these findings as the macrophage sensor could detect tumors up to 50-fold smaller in volume than possible with cfDNA mutation detection.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously correlated ctDNA abundance with cancer volume based on published empirical data. The minimum percent mutant allele fraction of circulating DNA needs to be around 0.01% in order for any method to detect ctDNA fragments with a 10 mL blood draw [4,5]. Below this fraction, there will be less than one tumor DNA genome equivalent in a 10 mL blood draw.…”
Section: Independent Effortsmentioning
confidence: 99%
“…For more details see Refs. [4] and [5]. Currently, imaging technologies can readily detect 6 mm diameter tumors [11].…”
Section: Independent Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the utility of ctDNA in advanced cancer [194][195][196][197]. In particular, ctDNA assays can capture a more global portrait of tumor heterogeneity than that provided by tissue DNA (which reflects the small piece of tissue that is biopsied rather than DNA shed from both primary and multiple metastatic sites [198]); therefore, ctDNA can be exploited to monitor tumor response and resistance.…”
Section: Confounding the Holy Grail-early Detection Of Cancer With Blmentioning
confidence: 99%